POTENSI PRODUK KARET PERKEBUNAN RENTENG PTPN XII DI JEMBER DALAM KONTRIBUSI TERHADAP FLUKTUASI KARET JAWA TIMUR - Mochammad Nasirudin; Mohammad Wimbo Raksagiri (UNEJ e-Proceeding)
Based on data from the FAO, Indonesia is the second producer of rubber in the world after Thailand. Although Indonesia is at the second position as the world rubber producing countries, Indonesia will be in the fifth position in rubber productivity. For East Java best rubber products rubber sheet categories of Jember with the brand "Renteng" which is the result Renteng factory PTPN XII in village districts Manggaran Ajung Jember district. Gardens Renteng PTPN XII is a rubber plantation The Jember and exported in German, English, French, American, Chekolosvia, and India. Sheet rubber production plant Renteng average of 912.5 tons / year, with the global market prices and the price of the American dollar annual revenue fluctuations. Lowest income to the rubber sheet "Renteng" in 2012 amounted to Rp. 13,406,939,000.00 and forecast 2016 earnings of rubber will happen largest revenue is Rp. 23,808,466,500.00. For contributions rubber sheet "Renteng" to rubber East Java in 2014 was 4.539%, 2015 was 4.639% and 2016 is 4.74%.